Effect of Heat Stress on Pregnancy Outcomes in Sprague Dawley Rats - Akmar Nadhirah Mohd Nor, Nur; Nizam Haron, Mohd; ., . (International Journal of Engineering and Technology, 2018)
Heat stressed animal may cause problem to the farmers as it will drop the production performance and reproductive efficiency such as animalâ€™s fertility and calving interval. In Malaysia, farmers tend to establish an open housing system or let their livestock to roam for grazing. Slightly increase in degree of hyperthermia from the environment factor could induce heat stress in animals. Hence, the aim of this study is to observe the effect of heat stress on pregnancy outcome in pregnant Sprague Dawley rats. Upon determination of oestrous, the female rats were mated. Once pregnancy was confirmed, the rats were divided into two groups. The treatment groups were exposed to the heat treatment at 41Â°C. While in control group, the rats were maintained at 24 Â°C. The treatment was given until delivery. Once delivered, the rats were euthanized. The reproductive organs were dissected and weighted. Pregnancy outcomes were observed and were seen to be affected. There was reduction in the reproductive organs weight which were the uterus and ovary, lower number of pup, alteration of offspring sex and also higher percentage of resorption. Although there was no significant finding between the two groups, but there was a pattern in the parameter observed that may indicate the effect of heat stress in pregnant rats. Therefore, heat stress may give negative effect to the pregnancy outcomes and reproductive system in rats.Â Â